151k views
2 votes
Simplify the expression below and leave your expression in exact form with coefficient a and radicand b so we have : a\sqrt[]{b} . Keep in mind that the coefficient a can be a product of a number and a variable.(4y^3)^{1/2}Our coefficient a = AnswerOur radicand b = Answer

Simplify the expression below and leave your expression in exact form with coefficient-example-1
User Bojangle
by
4.8k points

1 Answer

3 votes

Recall, 45 = 3 x 3 x 5 = 3^2 x 5

The expression would be


\begin{gathered} 15\sqrt[]{5}\text{ + 7}*\sqrt[]{3^2}\text{ }*\text{ }\sqrt[]{5} \\ =\text{ 15}\sqrt[]{5}\text{ + 7 }*3*\sqrt[]{5} \\ =\text{ 15}\sqrt[]{5}\text{ + 21}\sqrt[]{5} \\ =\text{ 36}\sqrt[]{5} \end{gathered}

Thus,

a = 36

b = 5

User HaveSpacesuit
by
5.6k points